Predictive performance of 'Servin's formula' during BIS-guided propofol-remifentanil target-controlled infusion in morbidly obese patients. - Albertin, A; Poli, D; La Colla, L; Gonfalini, M; Turi, S; Pasculli, N; La Colla, G; Bergonzi, P C; Dedola, E; Fermo, I (BJA: The British Journal of Anaesthesia, 2007)
Background: The aim of this study was to assess the predictive performance of 'Servin's formula' for bispectral index (BIS)-guided propofol-remifentanil target-controlled infusion (TCI) in morbidly obese patients.Methods: Twenty patients (ASA physical status II-III, age 32-64 yr) undergoing bilio-intestinal bypass surgery, were recruited. Anaesthesia was induced by using a TCI of propofol with an initial target plasma concentration of 6 microg ml(-1), then adapted to maintain stable BIS values ranging between 40 and 50. A TCI of remifentanil was added to achieve pain control and haemodynamic stability. For propofol, weight was corrected as suggested by Servin and colleagues. With ideal body weight (IBW) corrected according to formula suggested by Lemmens and colleagues. For remifentanil, weight was corrected according to IBW. Arterial blood samples for the determination of blood propofol concentrations were collected at different surgical times. The predictive performance of propofol TCI was evaluated by examining performance accuracy.Results: Median prediction error and median absolute prediction error were -32.6% (range -53.4%; -2.5%) and 33.1% (10.8%; 53.4%), respectively. Wobble median value was 5.9% (2.5%; 25.2%) while divergence median value was -1.5% h(-1) (-7.7; 33.8% h(-1)).Conclusion: Significant bias between predicted and measured plasma propofol concentrations was found while the low wobble values suggest that propofol TCI system is able to maintain stable drug concentrations over time. As already suggested before, a computer simulation confirmed that the TCI system performance could be significantly improved when total body weight is used.